2003
DOI: 10.1001/jama.290.13.1749
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin in Patients With Cystic Fibrosis Chronically Infected With Pseudomonas aeruginosa

Abstract: for the Macrolide Study Group C YSTIC FIBROSIS (CF) IS CHARacterized by a recurrent cycle of pulmonary infection and inflammation. Pseudomonas aeruginosa is the most common pathogen in patients with CF and by age 18 years, 80% of patients are chronically infected. Neutrophils are the dominant inflammatory cells and much of the airway destruction characteristic of CF is secondary to neutrophil-derived proteases and oxidants. 1 Treatment strategies for CF lung disease have included antibiotics, mucolytics, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
630
1
19

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 900 publications
(676 citation statements)
references
References 28 publications
(27 reference statements)
18
630
1
19
Order By: Relevance
“…The observed anti-virulence activity is likely to be involved in the clinical benefits associated with AZM treatment in the first year of therapy while the reduced efficacy associated with longer treatment duration might be due to development of bacterial resistance to AZM anti-virulence activity. Thereby, evaluation of molecules with similar antibacterial mechanisms is important to find alternative treatments for patients not responding to AZM or for whom the treatment lost efficacy during time [18,29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed anti-virulence activity is likely to be involved in the clinical benefits associated with AZM treatment in the first year of therapy while the reduced efficacy associated with longer treatment duration might be due to development of bacterial resistance to AZM anti-virulence activity. Thereby, evaluation of molecules with similar antibacterial mechanisms is important to find alternative treatments for patients not responding to AZM or for whom the treatment lost efficacy during time [18,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is a number of patients that do not benefit from AZM therapy or that show adverse effects to the drug [18]. Especially for these patients, it is important to find alternative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Subinhibitory concentrations of macrolides have been shown to be effective in inhibiting quorum-sensingdependent virulence both in vivo and in vitro (Imamura et al, 2004;Molinari et al, 1993;Sofer et al, 1999;Tateda et al, 2001). Furthermore, CF patients showed significant improvement in pulmonary function with the use of macrolides without any effect on the total Pseudomonas population (Fujii et al, 1995;Saiman et al, 2003). Despite its success in decreasing P. aeruginosa virulence, macrolides are not ideal because, like any other antibiotic, excessive usage is associated with bacterial resistance.…”
Section: C M Antunes and Othersmentioning
confidence: 99%
“…The possibility that macrolides might modify the neutrophilic inflammatory response in CF was first investigated in the early 2000s. Since then, a number of clinical trials have confirmed their beneficial effects both in adults and children [31][32][33][34][35][36][37]. Recently, in a multicentre, randomised, double-blind, placebo-controlled trial, 260 CF patients, not infected with P. aeruginosa, were randomised in a 1:1 ratio to azithromycin 250 mg or 500 mg (based on body weight) 3 days per week, or placebo, for a period of 24 weeks.…”
Section: Cystic Fibrosismentioning
confidence: 99%